REFLECTIVE JOURNALS AS SELF-ASSESSMENT TO PROMOTE STUDENTS’ WRITING SKILL - Ni’ma, Hanna Novariana Azizah (International Online Journal of Education and Teaching, 2020)
This research is experimental research with a 2x2 factorial design. In this study, the researcher took students of two classes as a sample of the research, one for the experimental group (EG) and the control group (CG). There were 32 students in each experimental and control class, so the total sample was 64 students. Both of these classes were considered to have English knowledge and writing skill at the same level. The samples of the experiment group taught by using a reflective journal and the control class taught by using the traditional writing method. And all these samples are viewed from students’ motivation. The sample was obtained by implementing a cluster random sampling technique. Each class was divided into two groups each of which consisted of 16 high motivation students and 16 low motivation students. the researcher used Multifactor Analysis of Variance (ANOVA) 2x2 to know the effects of the independent variables Reflective Journals and traditional writing method and attributive variable (Students’ Motivation) toward the dependent variable (Writing skill). And the research result reveals as follows; (1) Reflective Journals is more effective than traditional writing method to promote students’ writing. (2) Students have high motivation have better writing skill than those low motivation students. (3) There is an interaction between teaching assessment and students’ motivation to teach writing.